A novel, putatively null, FGD1 variant leading to Aarskog-Scott syndrome in a family from UAE. Issue 1 (December 2017) - Hamzeh, Abdul; Saif, Fatima; Nair, Pratibha; Binjab, Asma; Mohamed, Madiha; Al-Ali, Mahmoud; Bastaki, Fatma
Abstract Background The X-linked condition "Aarskog-Scott syndrome (AAS)" causes a characteristic combination of short stature, facial, genital and skeletal anomalies. Studies elucidated a causative link between AAS and mutations in the FGD1 gene, which encodes a Rho/Rac guanine exchange factor. FGD1 is involved in regulating signaling pathways that control cytoskeleton organization and embryogenesis. Case presentation FGD1 was studied in an Emirati family with two cases of AAS using PCR amplification and direct sequencing of the entire coding region of the gene. Various in silico tools were also used to predict the functional consequences of FGD1 mutations. In the reported family, two brothers harbor a novel hemizygous mutation in FGD1 c.53del (p.Pro18Argfs*106) for which the mother is heterozygous. This frameshift deletion, being close to N-terminus of FGD1, is predicted to shift the reading frame in a way that it translates to 105 erroneous amino acids followed by a premature stop codon at position 106. Full molecular and clinical accounts about the variant are given so as to expand molecular and phenotypical knowledge about this disorder. Conclusions A novel variant in FGD1 was found in an Emirati family with two brothers suffering from AAS. The variant is predicted to be a null mutation, and this is the first report of its kind from the United Arab Emirates.